2020
DOI: 10.1051/0004-6361/201937062
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variability and mass loss in Be stars

Abstract: Context. Be stars are physically complex systems that continue to challenge theory to understand their rapid rotation, complex variability, and decretion disks. γ Cassiopeiae (γ Cas) is one such star but is even more curious because of its unexplained hard thermal X-ray emission. Aims. We aim to examine the optical variability of γ Cas and thereby to shed more light on its puzzling behaviour. Methods. We analysed 321 archival Hα spectra from 2006 to 2017 to search for frequencies corresponding to the 203.5 day… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 68 publications
(103 reference statements)
4
28
0
Order By: Relevance
“…Using fifteen seasons of ground-based APT data, Smith et al (2006) and Henry & Smith (2012) detected a frequency of 0.82 d −1 with variable amplitude. The signal appeared lower in 2004-2011compared to 1997-2003. Borre et al (2020 confirmed these results using SMEI space-based data taken over the same years.…”
Section: Variability In Other Datasetssupporting
confidence: 76%
See 3 more Smart Citations
“…Using fifteen seasons of ground-based APT data, Smith et al (2006) and Henry & Smith (2012) detected a frequency of 0.82 d −1 with variable amplitude. The signal appeared lower in 2004-2011compared to 1997-2003. Borre et al (2020 confirmed these results using SMEI space-based data taken over the same years.…”
Section: Variability In Other Datasetssupporting
confidence: 76%
“…strength of this signal seems to have further fainted, becoming undetectable. The dominant frequency now seems to be a signal at 2.48 d −1 frequency (Borre et al 2020). The same authors also reported an additional signal at 1.25 d −1 as well as potential detections near 0.97 and 5.06 d −1 .…”
Section: Variability In Other Datasetsmentioning
confidence: 69%
See 2 more Smart Citations
“…HD 45910 is a known interacting binary system (Koubský et al 2012(Koubský et al , 2011, whereas Cas is also suggested to be a binary system having a possible compact object as a companion (Smith et al 2017). On the contrary, Borre et al (2020) suggested that the X-ray emission in case of Cas might be coming from the CBe star itself, thus ruling out the binarity scenario.…”
Section: Ca Triplet Line Formation Region: Possibility Of Binaritymentioning
confidence: 99%